Rh(III)-catalyzed C−H alkylation of indolines with enones through conjugate addition and protonation pathway. Issue 32 (10th August 2017) - Oh, Hyunjung; Park, Jihye; Han, Sang Hoon; Mishra, Neeraj Kumar; Lee, Suk Hun; Oh, Yongguk; Jeon, Mijin; Seong, Gyeong-Joo; Chung, Ka Young; Kim, In Su
Abstract: The rhodium(III)-catalyzed C−H alkylations of indolines with enones and enals is described. This reaction can proceed through 1, 4-conjugate addition and protonation process providing β-indolinic ketone compounds, which are known to be crucial scaffolds of biologically active compounds. Graphical abstract: